Komunitas Young Interfaith Peacemaker Community (YIPC) di Kota Medan - Jimly Qardhawi Gultom; Ibrahim Gultom; Erond Litno Damanik (Jurnal Antropologi Sumatera, 2022)
The YIPC community is a national scale interfaith peace community. The YIPC center is in Yogyakarta and has several regions, one of which is in Medan. As a community that is quite large and consists of several religious backgrounds, it will have its own challenges in maintaining the existence of its community. One of the ways is by strengthening integration among YIPC members. The solid integration within the group can be reflected in the interaction and communication between group members. Therefore, this research is focused on exploring further about communication within the YIPC community. The research method used is a qualitative approach. The unit of analysis is the Medan Regional YIPC community. Regional routine activities carried out are Scriptural reasoning and weekly discussions, Peace Camp (PC), Holding various social actions, Training for facilitators, commemorating religious holidays and Commemorating International Day of Peace.